2017
DOI: 10.1088/1475-7516/2017/08/009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling CMB lensing cross correlations with CLEFT

Abstract: Abstract.A new generation of surveys will soon map large fractions of sky to ever greater depths and their science goals can be enhanced by exploiting cross correlations between them. In this paper we study cross correlations between the lensing of the CMB and biased tracers of large-scale structure at high z. We motivate the need for more sophisticated bias models for modeling increasingly biased tracers at these redshifts and propose the use of perturbation theories, specifically Convolution Lagrangian Effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 176 publications
4
70
1
Order By: Relevance
“…However, this assumption increasingly breaks down as dynamics and bias become nonlinear at low redshift and high mass ( Fig. 4; see also Modi et al 2017;Wilson & White 2019). The model of Eq.…”
Section: Common Bias Modelmentioning
confidence: 99%
“…However, this assumption increasingly breaks down as dynamics and bias become nonlinear at low redshift and high mass ( Fig. 4; see also Modi et al 2017;Wilson & White 2019). The model of Eq.…”
Section: Common Bias Modelmentioning
confidence: 99%
“…Similarly to the case of biased tracers, the EFT [47,62] provides a standard expansion for the matter field, i.e. what is needed to make theoretical predictions of gravitational lensing (e.g [63,64]). Up to third order, this is given by…”
Section: Review Of Bias Expansion For Scalar Tracersmentioning
confidence: 99%
“…In order to optimize what can be learned from the surveys mentioned above, theoretical predictions in the mildly and fully non-linear regimes are also needed. Previous work has suggested that perturbative models can accurately predict the clustering of biased tracers to a significant fraction of the nonlinear scale k nl = Σ −1 at high z [55][56][57][58][59], where Σ is mean square one-dimensional displacement in the Zeldovich approximation given by with P L the linear theory power spectrum. For high redshift tracers such as HI, perturbative models with their sophisticated biasing schemes become more useful due to increasing complexity of bias and decreasing non-linearity of the matter field as we go further back in time [59].…”
Section: Hi Clusteringmentioning
confidence: 99%
“…Previous work has suggested that perturbative models can accurately predict the clustering of biased tracers to a significant fraction of the nonlinear scale k nl = Σ −1 at high z [55][56][57][58][59], where Σ is mean square one-dimensional displacement in the Zeldovich approximation given by with P L the linear theory power spectrum. For high redshift tracers such as HI, perturbative models with their sophisticated biasing schemes become more useful due to increasing complexity of bias and decreasing non-linearity of the matter field as we go further back in time [59]. While we leave a detailed study of modeling 21-cm signal with such models for future work, when more sophisticated models and more simulation volume could become available, here we will compare the clustering signal to the predictions of linear theory and 'Zeldovich effective field theory' (ZEFT [60]).…”
Section: Hi Clusteringmentioning
confidence: 99%